FACTORS THAT ENCOURAGE COMMUNITY INTEREST IN USING QUICK RESPONSE CODE TO DONATE FOR ZIS IN BAZNAS CIREBON DISTRICT - Dede Al Mustaqim; Nazula Alfi Rahmah (Institut Agama Islam Negeri Metro, 2025)
This study aims to explore the factors driving the public interest in using Quick Response Code (QRIS) as a means to donate Zakat, Infaq, and Sadaqah (ZIS) to the National Amil Zakat Agency (Baznas) in Cirebon Regency. The research method employed was qualitative. Data collection involved administering questionnaires to 126 respondents, conducting direct interviews with 8 community members, and interviewing an expert in zakat and waqf management. The findings of the study highlight several key factors influencing public interest in donating ZIS via QRIS, including the level of trust in Baznas and the QRIS system, the proximity of QRIS donation locations facilitating access, the convenience and ease of use of QRIS, civil servant status, and well-organized ZIS donation programs. The implications of these findings indicate the necessity for Baznas in Cirebon Regency to enhance public trust in the institution and the QRIS payment system, expand the network of QRIS donation locations in easily accessible areas, ensure comfortable and user-friendly QRIS usage, involve civil servants in promoting and implementing ZIS donation programs via QRIS, and organize ZIS donation programs in a planned and structured manner. By taking these steps, it is hoped that public interest in using QRIS to donate ZIS to Baznas in Cirebon Regency will significantly increase, ultimately supporting the institution's revenue growth and poverty alleviation efforts in the region.